2017
DOI: 10.1021/acs.langmuir.6b04282
|View full text |Cite
|
Sign up to set email alerts
|

Three-Legged 2,2′-Bipyridine Monomer at the Air/Water Interface: Monolayer Structure and Reactions with Ni(II) Ions from the Subphase

Abstract: The behavior of compound 2 [1,3,5-tri(2,2'-bipyridin-5-yl)benzene] with three bipyridine units arranged in a star geometry is investigated in the presence and absence of Ni(ClO). Its properties at the air-water interface as well as after transfer onto a solid substrate are studied by several techniques including Brewster angle microscopy, X-ray reflectivity, neutron reflectivity, X-ray photoelectron spectroscopy, Rutherford backscattering spectrometry, and atomic force microscopy combined with optical microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The Langmuir technique is ideally suited for preparing 2D materials of non-water or partially water soluble precursors. It allows for positioning of reactive end groups of monomers at the air-water interface for linking by different reaction mechanisms such as by irradiation [34], enzyme [35], catalyst [36], metal ions [37,38] and 'click' reactions [39]. Additionally, faster analysis of biodegradation processes are possible by this technique at molecular level [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Langmuir technique is ideally suited for preparing 2D materials of non-water or partially water soluble precursors. It allows for positioning of reactive end groups of monomers at the air-water interface for linking by different reaction mechanisms such as by irradiation [34], enzyme [35], catalyst [36], metal ions [37,38] and 'click' reactions [39]. Additionally, faster analysis of biodegradation processes are possible by this technique at molecular level [40].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, faster analysis of biodegradation processes are possible by this technique at molecular level [40]. While various ideally symmetric, small molecules are linked using Langmuir technique to form 2D materials [34,37,39,[41][42][43][44], only few studies described 2D cross-linking of oligomers or polymers using the Langmuir technique in recent years [5,38,[45][46][47][48][49]. For example, a semiinterpenetrating oligomeric network is achievable by embedding cross-linked methacryloxypropyl-terminated polydimethylsiloxane in a cellulose acetate butyrate matrix [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several reactions have been explored for the interfacial synthesis of 2DPs [18–21] . For instance, [4+4] anthracene dimerization, Schiff‐base condensation reactions and Glaser–Hey coupling reactions [22–30] . Although several examples of ultrathin 2DPs have been successfully prepared through interfacial synthesis, it's still urgent to find a more exquisite design of the monomers with better pre‐assembled properties and explore new chemical reactions to synthesize highly crystalline 2DPs in more facile and controllable ways [31, 32] .…”
Section: Figurementioning
confidence: 99%
“…[18][19][20][21] For instance,[ 4 + +4] anthracene dimerization, Schiff-base condensa-tion reactions andG laser-Hey coupling reactions. [22][23][24][25][26][27][28][29][30] Althoughs everal examples of ultrathin 2DPs have been successfully prepared through interfacial synthesis, it's still urgent to find am ore exquisite design of the monomers with betterp reassembled properties and explore new chemical reactions to synthesize highlyc rystalline 2DPs in more facile and controllable ways. [31,32] Photo-triggered [2+ +2] cycloaddition reactions have been provedt os how great potential in the topochemical control in the solid-state.…”
mentioning
confidence: 99%
“…out of 2D polymers is of significant interest. The behavior of compound 2 [1,3,5-tri(2,2 -bipyridin-5-yl)benzene] with three bipyridine units arranged in a star geometry was investigated in the presence and absence of Ni(ClO 4 ) 2 by XRR [190]. It was found that the compound 2 stays almost vertical at the interface and at high Ni 2+ /2 ratios, two of the three bipyridine units are complexed, resulting in supramolecular sheets that are likely composed of arrays of linear metal-organic complex of the polymer.…”
Section: Liquid Interfacesmentioning
confidence: 99%